Efeito da heterogeneidade ambiental em populações naturais de duas espécies arbóreas congenéricas e suas implicações para o manejo e conservação da vegetação ripária - Allan de Freitas Magalhaes (2011)
As important as elucidating effects of the environment where mother plant is, it is also important to know the adaptive capacity in distinct habitats, i.e., the mechanisms used to establish in riparian environments. There is few available information about tree species that occur in riparian ecosystem, which environmental gradient is crucial to the adaptation in these ecotones. Therefore, studies about vegetal species present in these areas are fundamental to a better comprehension of populational dynamics of plants and vegetal communities. This study aimed to know the possible relationship between genetic diversity and biochemical and morphological alterations of reproductive structures. This information will allow us to define implications under management and conservation of vegetal species occurring in riparian environments regarding the propagule collect and genetic diversity of their subpopulations. Species are distributed in two Conservation Unities, Byrsonima verbascifolia (L.) DC at Parque Estadual do Rio Doce PERD and Byrsonima intermedia A. Juss. at Estação Ambiental de Peti - PETI. Two plants subpopulations were defined according to riparian microhabitats, the subpopulation submitted to the flood regime and higher luminosity on the canopy, by the edge effect, are located in the microhabitat margin (MMA); in the middle microhabitat (MME) there are tree individuals distributed within the vegetation, without flooding. According to the results, we observed that luminosity on the canopy varies according to ecological behaviorof vegetal communities, which is directly associated to flooding pulse. The soil of microhabitats differed, on PETI it was characterized by young soils that presented higher fertility at microhabitat MMA, while onPERD, characterized by older soils, they are more fertile at microhabitat MME. We observed morphological variation on dimensional characters of reproductive structures in subpopulations of distinct microhabitats, B.intermédia varies on length, diameter and fruit volume and B. verbascifolia varies on effective and total length of the bunch, length and diameter of diaspore. B. intermedia and B. verbascifolia produced morepropagules on microhabitats of lower fertility. Subpopulations presented low genetic diversity (B. intermedia MMA He=0.428; MME He=0.434 and B. verbascifolia MMA He=0.362; MME He=0.370), gene flow (Nm) was about 4.8 for subpopulations of B. intermedia and 4.7 for B. verbascifolia. The studied species presented distinct morphoanatomical plasticity according to the micrihabitats. In both species palisade parenchymapresented higher dimensional variation according to the microhabitat, compared to the spongy parenchyma. Length and diameter of stomata were significantly different for B. intermedia and partly for B. verbascifolia.This indicates a higher plasticity of B. intermedia when compared to B. verbascifolia. Leaf thickness of B.intermedia presented a higher proportion of palisade parenchyma, while B. verbascifolia showed greaterthickness of spongy parenchyma. Greater morphoanatomical variations were found at micrihabitat MMA, what can be due to the greater variety of natural resources, such as luminosity and hydric availability. Individuals of B. intermedia and B. verbascifolia present at microhabitats MMA allocates more water, protein, lipids and crude fiber when compared to the ones from MME. Greater contents of polyphenols were found on populations farther from the water body (B. intermedia=0.097%; B.verbascifolia=0.141%), suggesting a greater susceptibility to herbivory. Ecophysiological studies revealed that the initial hhumidity of propagative structure from B. intermédia varied considerably amog compartments, and the seeds reached a maximum value of 10%. The assessment of rate of seeds and diaspore imbibitions showed that propagativestructures followed a three-phase pattern with total period of 216 hours. At MMA studied area under flooding regime, regenerants of B. intermedia were observed. The enbrio growing stages are characterized by the disruption of diaspore by the primary root and growing of epicotyls, stretch and extension of cotyledons and pigmentations of their tissues, stiffening of cotyledons and epicotyls and extension of the second pair of cotyledons. The total period of seedling lasted 21 days. Once these behaviors known subpopulation in microenvironments, higher standards on the collection of propagules to use these individuals as seeds bearing will allow more appropriate management and conservation of their populations if they are used in plant restoration programs in these areas.